Digitalisasi UMKM, Literasi Keuangan, dan Kinerja Keuangan : Studi pada masa Pandemi COVID-19 - Larissa Adella Octavina; Maria Rio Rita (STIE Perbanas Surabaya, 2021)
The purpose of this study is to analyze the significance of UMKM’s digitized influence, financial literacy, and financial performance comprising some constructive, which is : fintech based payment gateway, digital marketing, and financial literacy. The kind of research used a quantitative approach. Using the online distribution of the questionnaire using 118 samples taken by umkm in the culinary sector in The City of Solo. The data analysis techniques used in the study are moderated regression analysis equations (MRA) tested by using SPSS software. The results showed a significant positive impact between UMKM’s financial performance, digital marketing had a significant positive impact on financial performance of UMKM, and financial literature could moderated the most fintech based payment gateway.